Genetic Divergence and Phylogenetic Relationships Among Indonesian Species of Monitor Lizards of the Genus Varanus Based on Cytochrome Oxidase I Sequences - Evy Arida (Bogor Agricultural University, Indonesia, 2017)
The application of cytochrome oxidase subunit I for genetic divergence and phylogenetic analyses in monitor lizards seems to be limited, despite the practicality and relevance to use the short sequence of this region known as the DNA barcode. Some Indonesian species of monitor lizards are morphologically similar, some of which are legally exported as pet animal commodities and some others being protected by Indonesian national law. Thus, a practical molecular tool that can be useful to help clarify their species identity is essential, especially for closely related species. This study used the DNA barcode to test the application of this mitochondrial DNA region as a molecular tool to identify some species of Indonesian monitor lizards for the first time. Results showed that the Barcodes can facilitate molecular speciesidentification based on their relative amount of genetic divergence and phylogenetic relationships. Closely related species can be distinguished based on the short sequences, as well as a likelihood of species misidentification among samples in this study. Further study should be performed in the future using more species, especially those belong to groups of species complex from the eastern Indonesia and species protected by the Indonesian national law.